Marine microbial bioprospecting: Exploitation of marine biodiversity towards biotechnological applications—a review - Hoda Hosseini (16932462) (2022)
The increase in the human population causes an increase in the demand for nutritional supplies and energy resources. Thus, the novel, natural, and renewable resources became of great interest. Here comes the optimistic role of bioprospecting as a promising tool to isolate novel and interesting molecules and microorganisms from the marine environment as alternatives to the existing resources. Bioprospecting of marine metabolites and microorganisms with high biotechnological potentials has gained wide interest due to the variability and richness of the marine environment. Indeed, the existence of extreme conditions that increases the adaptability of marine organisms, especially planktons, allow the presence of interesting biological species that are able to produce novel compounds with multiple health benefits and high economical value. This review aims to provide a comprehensive overview of marine microbial bioprospecting as a growing field of interest. It emphasizes functional bioprospecting that facilitates the discovery of interesting metabolites. Marine bioprospecting was also discussed from a legal aspect for the first time, focusing on the shortcomings of international law. We also summarized the challenges facing bioprospecting in the marine environment including economic feasibility issues. Other Information Published in: Journal of Basic Microbiology License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1002/jobm.202100504